Is the influence of quality of work life on innovative work behavior mediated by happiness at work in teachers - Hasanati, Nida; Karima, Azizah Khusnul; Surahman, Surahman (Jurnal Ilmiah Psikologi Terapan, 2025)
The innovative work behaviour of teachers is critical in creating a dynamic learning environment, increasing student engagement and motivation, and encouraging professional development. Innovation not only benefits students but also helps teachers develop and adapt to face challenges in the world of modern education. Quality of work life is assumed to influence innovative behaviour at work but does not influence it directly. Therefore, this research uses happiness as a mediator variable. This research aims to determine the influence of quality of life on teachers' innovative behaviour, which is mediated by happiness at work. The research subjects were 119 people who worked as teachers in primary, junior, secondary and senior secondary schools. The instruments used are the quality of work-life scale, happiness at work scale and innovative work behaviour scale. Data analysis uses regression analysis techniques with mediation. The results show no direct influence of the quality of work life on innovative behaviour at work. However, it was found that happiness at work fully mediates the influence of the quality of work life on innovative behaviour at work. The expected implication is to make teachers feel happy by increasing the quality of life at work.